The beneficial effect of weight reduction on adverse cardiovascular outcomes following bariatric surgery is attenuated in patients with obstructive sleep apnea. Issue 5 (7th February 2018) - Dalmar, Ahmed; Singh, Maharaj; Pandey, Bennet; Stoming, Christopher; Heis, Zoe; Ammar, Khawaja Afzal; Jan, M Fuad; Choudhuri, Indrajit; Chua, Thomas Y; Sra, Jasbir; Tajik, A Jamil; Jahangir, Arshad
Abstract: Weight loss after bariatric surgery is associated with reduction in adverse cardiovascular outcomes; however, the impact of obstructive sleep apnea (OSA) on reduction of cardiovascular outcomes after bariatric surgery in morbidly obese patients is not known. We retrospectively assessed differences in cardiovascular events after laparoscopic adjustable gastric banding (LAGB)–induced weight loss in patients with and without OSA before and after propensity score matching for age, sex, body mass index (BMI), and major comorbidities between the two groups and determined predictors of poor outcomes. OSA was present in 222 out of 830 patients (27 per cent) who underwent LAGB between 2001 and 2011. Despite a similar reduction in BMI (20.0 and 20.8 per cent), a significantly higher percentage of cardiovascular events were observed in patients with than without OSA (35.6 vs 6.9 per cent; p < 0.001) at 3 years (mean follow-up 6.0 ± 3.2; range: 0.5 to 13 years). The differences in the cumulative endpoint of new onset stroke, heart failure, myocardial infarction, venous thrombosis, and pulmonary embolism between the OSA and non-OSA groups were maintained after propensity matching. Patients with OSA treated with continuous positive airway pressure (CPAP) during sleep [ n = 66] had lower cardiovascular event rates at 30 months compared with those not treated ( p < 0.041). OSA (hazard ratio: 6.92, 95% CI: 3.39–14.13, p < 0.001) remained an independent predictor of cardiovascular events after multivariate analysis. Thus, patients with OSA, despite a similar initial weight loss after LAGB, had a higher incidence of cardiovascular events compared with a propensity-matched group without OSA. Treatment with CPAP appears to reduce such events.